On the Potentials of Artificial Intelligence in Marketing – The Case of Robotic Process Automation (International Journal of Applied Research in Management and Economics, 2021)
The various applications of AI have not yet led to widespread acceptance in marketing. Nevertheless, AI has enormous potential to fundamentally change the field of marketing with its applications, making the topic highly relevant for companies. By analyzing current applications, potential use cases in the near future, implementation opportunities and optimization areas, the study can present a comprehensive understanding of the long-term impact of AI in marketing and on marketing as a discipline. In particular, it looks at potential applications and challenges for companies that provide insight into the future of marketing. These are relevant to remain competitive in the future. In particular, the sub-area of Robotic Process Automation (RPA) will be addressed. For this purpose, two research questions were posed. On the one hand, the use cases in marketing that are given by the automation of processes by means of AI are examined. Secondly, the question is posed as to how the potential of AI in marketing can be further expanded and what trends can be identified or what significance RPA forms in this context. The analysis is based on a qualitative survey in the form of interviews with experts from the field.